2022
DOI: 10.1515/htmp-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical production of silicon

Abstract: Silicon solar cells are crucial devices for generating renewable energy to promote the energy and environmental fields. Presently, high-purity silicon, which is employed in solar cells, is manufactured commercially via the Siemens process. This process is based on hydrogen reduction and/or the thermal decomposition of trichlorosilane gas. The electrochemical process of producing silicon has attracted enormous attention as an alternative to the existing Siemens process. Thus, this article reviews different scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 215 publications
0
15
0
Order By: Relevance
“…[105,111,113,138] However, electrodeposition of silicon at different electrode surfaces at room temperature is in the focus of research, and already covered by comprehensive reviews. [31][32][33][34]…”
Section: Sià Si Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[105,111,113,138] However, electrodeposition of silicon at different electrode surfaces at room temperature is in the focus of research, and already covered by comprehensive reviews. [31][32][33][34]…”
Section: Sià Si Bond Formationmentioning
confidence: 99%
“…[20] While the field of electrochemical synthesis of organosilanes and silane compounds is constantly expanding and new, exciting concepts are being published, to our knowledge, no review has appeared since 2000 on the holistic view of synthesis routes starting from hydro-and halosilanes. [21][22][23][24][25][26] Whereas there are reviews regarding the electrochemical synthesis of organosilicon species, [2,[21][22][23][24][25][26][27][28] formation of polysilanes, [29,30] the electro-deposition of silicon starting from halosilanes, [31][32][33][34] and silyl radical driven conversions, [35] this review is focused on the electrochemical Si bond formation starting from chloro-and hydrosilanes. Ionic as well as the radical related type of conversion are the scope of the present analysis, further providing a general view on common obstacles regarding the work with chloro-and hydrosilanes.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional Si substrate manufacturing methods have major drawbacks, such as low productivity with the Siemens method and a large kerf loss with the Si slice method. With the increasing demand for crystalline Si solar cells, there is a strong need to develop alternative manufacturing methods for Si substrates. , A promising method is the direct formation of Si films on inexpensive substrates. We investigated the electrodeposition of Si using a KF–KCl molten salt.…”
Section: Electrodeposition Of Siliconmentioning
confidence: 99%
“…In the 1970s and 1980s, it has been reported that crystalline silicon was electrodeposited in the fluoride melts containing K 2 SiF 6 . Electrodeposition of silicon from SiO 2 in chloride melts , and from SiCl 4 in chloride–fluoride melts was also investigated. Recently, the review of the silicon electrodeposition in high-temperature molten salt has been reported in some papers. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the review of the silicon electrodeposition in high-temperature molten salt has been reported in some papers. 12,13 In the electrodeposition process of silicon in high-temperature molten salt, fluoride melt has advantages in that it is the medium for electrowinning of Si directly from SiO 2 because of the high solubility of its metal oxides at relatively lower temperatures. The authors have reported that silicon film can be obtained by electrochemical reduction of SiO 2 in LiF− NaF−KF at 873 K. 14,15 By using nonconsumable oxygenevolving materials such as boron-doped diamond 16 and conductive ceramics 17 for anodes and electrical power derived from renewable energy sources for supplying the electricity needed for heating molten salts and conducting electrolysis, it is possible to construct a silicon manufacturing process without carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%